Kemampuan Diuretik Ekstrak Etanol Buah Sukun (Artocarpus Altilis) Pada Tikus - Windarsih, Windarsih; , Nurcahyanti W., M.Biomed., Apt (2017)
Leaves of breadfruit (Artocarpus altilis) is one genus with jackfruit plant (Artocarpus heterophyllus) which has a diuretic effect. Breadfruit leaves contain quercetin compounds that has an effect to shed urine. Quercetin has a diuretic effect and breadfruit contains quercetin. This study aimed to test the diuretic effect of ethanol extract of breadfruit. A total of 30 rats were divided into six groups consisting of a negative control group (CMC Na 0,5%), urea control, furosemide, and breadfruit ethanol extract dose of 200 mg/kgBW, 800 mg/kgBW, and 3200 mg/kgBW. Giving each treatment group a total of 5 mL /kgBW and was given 50 mL of 0,9% NaCl, then put in metabolic cages. Based on volume cumulative of urine for 5 hours and 24 hours, the value lipschitz was calculated, AUC (Area Under the Curve) were tested statistically by ANOVA (Analysis of Variance) and LSD (Least Significant Difference) with 95% of trust level. The breadfruit ethanol extract dose of 3200 mg/kgBW was able to provide a diuretic effect in 1st -5th hour and 1st -24th hour with lipschitz value of 1,01 and 1,47. Urine volume can be increased from the normal control by the ethanol extract of breadfruit dose of 3200 mg/kgBW to result AUC1-5 3,35 ml.hour and AUC1-24 38,60 ml.hour. The breadfruit ethanol extract dose of 200 mg/kgBW dan 800 mg/kgBW have not shown their diuretic effect.